EFFECTS OF REAFFORESTATION BY EUCALYPTUS-GLOBULUS ON THE EDAPHIC COLLEMBOLA (REVUE D ECOLOGIE ET DE BIOLOGIE DU SOL, 1991)
The authors studied the effects of reafforestation by Eucalyptus globulus on the edaphic Collembola, by means of factorial analysis of correspondences applied to the study of Collembola populations, occurring in coppices of Quercus suber and in Eucalyptus globulus plantations.